Role of Telepathology, Artificial Intelligence, and Emerging Technologies in Enhancing Diagnostic Accuracy - Yugeshwari R. Tiwade; Obaid Noman; Pratibha Dawande; Nandkishor J Bankar; Sweta Bahadure; Praful Patil (Journal of Nature and Science of Medicine, 2025)
Telepathology, a practice of telecommunication-based pathology, has transformed the diagnostic process by allowing pathologists to remotely examine samples using video displays instead of traditional optical microscopes. Despite these challenges, the future holds significant potential with advances in artificial intelligence (AI) and innovations in augmented reality (AR) and virtual reality (VR). These technologies promise to revolutionize telepathology by enhancing diagnostic accuracy, providing immersive training experiences, and improving remote consultations. Telepathology greatly minimizes diagnosis errors and turnaround times, allowing quick consultations and second opinions in critical health situations. The technology can be used in routine histopathology, consultations, quality assurance, education, and research. This study investigates the efficacy of telepathology in improving diagnostic accuracy, especially in underserved areas where access to specialist pathology services is limited. With AI-driven analytics and AR/VR-assisted visualization, telepathology significantly enhances the precision of pathological diagnosis through remote consultation, second opinions, and intraoperative feedback.